2019
DOI: 10.4103/2224-3151.264855
|View full text |Cite
|
Sign up to set email alerts
|

Gendered perceptions of physical activity and diabetes in rural Bangladesh: a qualitative study to inform mHealth and community mobilization interventions

Abstract: Background Diabetes prevalence is increasing rapidly in Bangladesh, and there is an urgent need to promote preventive behaviours for type 2 diabetes, such as maintaining a healthy body weight, eating healthily, avoiding tobacco and being active for 150 minutes per week. Methods We used a qualitative methodology informed by the capability, opportunity, motivation theory of behaviour change to explore the factors affecting physical activity among men and women in rural Bangladesh. We conducted semi-structured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Although younger men seemed to support female household members, older men were reluctant. This finding is consistent with previous studies from Nepal (Kadariya & Aro, 2018; Oli et al, 2018), South Asia (Medagama & Galgomuwa, 2018; Morrison et al, 2019), Saudi Arabia (Al-Hazzaa, 2018), and migrant Indians (Ramanathan & Crocker, 2009), which have reported gender norms, cultural expectations, and family responsibilities limited women’s PA participation. The patriarchal setting in many South Asian communities seldom allocates decision-making power to women (Herath, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although younger men seemed to support female household members, older men were reluctant. This finding is consistent with previous studies from Nepal (Kadariya & Aro, 2018; Oli et al, 2018), South Asia (Medagama & Galgomuwa, 2018; Morrison et al, 2019), Saudi Arabia (Al-Hazzaa, 2018), and migrant Indians (Ramanathan & Crocker, 2009), which have reported gender norms, cultural expectations, and family responsibilities limited women’s PA participation. The patriarchal setting in many South Asian communities seldom allocates decision-making power to women (Herath, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…A Sri Lankan study (Medagama & Galgomuwa, 2018) has also reported that puddles, uneven roads and pavements, and being chased by unrestrained animals (e.g., stray dogs) limited PA participation. Another study from Bangladesh has reported that women feared falling over on muddy roads and uneven paths and the resultant embarrassment, which in turn discouraged PA participation (Morrison et al, 2019). This further reinforces the need for multisectoral collaboration in ensuring PA-friendly built environment.…”
Section: Discussionmentioning
confidence: 99%
“…Our formative research showed that before the intervention, women often felt unable to walk for exercise because they were not allowed by their husbands, they were too embarrassed, they felt unsafe, or they were afraid of social criticism [21]. Men and women were also afraid that people would think they had diabetes if they walked.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in Bangladesh, purdah (female seclusion), restricts women’s freedom of movement and their access to public spaces. Women are expected to behave demurely, avoid attracting attention from men, and uphold family honour [21]. Norms about the division of labour within and outside the household, as well as norms about movement outside the household are highly gendered [22].…”
Section: Methodsmentioning
confidence: 99%
“…(Iran) [60] "Women reported that it was considered inappropriate for them to walk on muddy roads and that they were afraid of slipping." (Bangladesh) [41]…”
Section: Natural Contextmentioning
confidence: 99%